1983
DOI: 10.1002/food.19830270702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cereal, fungal and bacterial α‐amylase on the rheological and breadmaking properties of medium‐protein wheats

Abstract: Optimal levels of cereal malt, fungal and bacterial cc-amylase for baking of medium-protein flours were found to be 5-10, 20 and 0.35 SKBjlOO g, respectively. The dough consistency decreased considerably with time, depending on the source and level of cc-amylase. The paste viscosities of the flours were reduced considerably by the cereal malts even at ?.5 SKBjlOO g than by the fungal and bacterial x-amylase used optimally. Satisfactory loaf volumes were obtained with optimised a-amylase supplements without ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…3d). An improvement in loaf volume has also been reported [16,17]. The crumb grain also improved to a similar extent as that observed for SSL.…”
Section: Quality Of Breadsupporting
confidence: 66%
“…3d). An improvement in loaf volume has also been reported [16,17]. The crumb grain also improved to a similar extent as that observed for SSL.…”
Section: Quality Of Breadsupporting
confidence: 66%
“…Bacterial a-amylase was reported to be stable up to 95 C whereas fungal a-amylase was reported to be stable up to 65 C (Anderson, Adams, & Walter, 1983;Miller, Johnson, & Palmer, 1953). Harinder, Maninder, and Bains (1983) reported that dough incorporated with fungal a-amylase had low paste viscosity compared to control and more than dough treated with bacterial a-amylase.…”
Section: Influence Of Enzymes On Amylograph Studies Of Chapatismentioning
confidence: 97%
“…Their activities were checked by the International Association for Cereal Chemistry (Perten 1966) method. To find out the optimum level of supplementation, preliminary trials were conducted according to the study of Harinder et al(1983). The amount equivalent to 80,200 and 5 SKB kg-l was found to be optimal for wheat malt, fungal and bacterial aamylases, respectively.…”
Section: Amylase Supplementsmentioning
confidence: 99%
“…Wheat malt pastes irrespective of level of GMS exhibited extremely low paste viscosities as compared with fungal and bacterial a-amylases. This can be attributed to extensive and drastic dextrinisation of starch even at very low levels of supplementation of wheat malt a-amylase (Harinder et al 1983).…”
Section: Amylograph Curve Characteristicsmentioning
confidence: 99%